Using picoliter droplet deposition to track clonal competition in adherent and organoid cancer cell cultures - Selami Baglamis; Vivek M. Sheraton; Debora Meijer; Haibin Qian; Ron A. Hoebe; Kristiaan J Lenos; Max A. Betjes; Max A. Betjes; Sander Tans; Jeroen van Zon; Louis Vermeulen; Przemek M. Krawczyk (Scientific Reports, 2023)
Abstract Clonal growth and competition underlie processes of key relevance in etiology, progression and therapy response across all cancers. Here, we demonstrate a novel experimental approach, based on multi-color, fluorescent tagging of cell nuclei, in combination with picoliter droplet deposition, to study the clonal dynamics in two- and three-dimensional cell cultures. The method allows for the simultaneous visualization and analysis of multiple clones in individual multi-clonal colonies, providing a powerful tool for studying clonal dynamics and identifying clonal populations with distinct characteristics. Results of our experiments validate the utility of the method in studying clonal dynamics in vitro, and reveal differences in key aspects of clonal behavior of different cancer cell lines in monoculture conditions, as well as in co-cultures with stromal fibroblasts.